Internationalization of the training and production of Brazilian Graduate Programs of Political Science - Rafael Machado Madeira (Revista Mexicana de Ciencias Políticas y Sociales)
This article analyzes the internationalization strategies of the teaching careers of Brazilian political scientists. Internationalization will be measured in two dimensions: 1) publications and 2) academic training of the teachers. Are the central countries the main destinations of Brazilian political scientists? In the field of Brazilian political science, do the central programs monopolize internationalization or is it also accessible to more recent programs? The hypothesis tested is that internationalization would be linked to the central countries and that core programs would be largely over-represented. The study analyzed 360 researchers linked to political science programs. The hypothesis was only partially confirmed.  It was concluded that the peripheral programs also have space in the internationalization of the academic training and in the publication of papers abroad. The main difference found between internationalization dynamics concerns the country of destination for academic training and for paper publication. Academic training is basically concentrated in central countries (US, England and France). Although it is absent in academic training Latin America has an important presence as a focus of the international publication of the researchers examined.